Management Of English Learning In Senior High Boarding School (Qualitative Descriptive Study Of Strategies To Improve The Quality Of Speaking Skills At Nahdlatul Wathan Bogor High School And Azzhahiriyah Islamic High School Bekasi) - Romdanih, Romdanih; Wasliman, Iim; Suhendraya, Hendi; Rostini, Deti (International Journal of Educational Research & Social Sciences, 2022)
The problem in this study is that the management of learning English at Pondok Senior High School is not good. The general research objective is to identify and describe the quality management of speaking skills in English language learning at Islamic boarding schools. Results of the study: In general, the management of learning English at Islamic Boarding School High Schools on the Strategy for Improving the Quality of Speaking Skills at Nahdatul Wathan Bogor High School and Azzhahiriyah Bekasi Islamic High School is going well, although there are some deficiencies in the aspects of Syllabus and RPP, strategy, strategy implementation, evaluation, and innovative efforts made to improve the quality of English speaking skills. The specific conclusions are: (1) Syllabus and lesson plans for learning English speaking skills at Pondok Senior High School, including: Learning syllabus, learning lesson plans, learning materials, learning methods, learning media, learning evaluation, and learning success standards have been well prepared. (2) The strategy for improving the quality of teaching English speaking skills at Pondok Senior High School includes: Internal strategy and external strategy have been well implemented. (3) Implementation of a strategy to improve the quality of teaching English speaking skills at Pondok Senior High School, including: Internal strategy consisting of increasing the competence of English teachers, providing English learning media, and intracurricular and extracurricular activities. The external strategy consisting of partnerships with other institutions and developing sister schools has been well implemented. (4) Evaluation of the Implementation of the Strategy for improving the quality of teaching English speaking skills at Pondok Senior High School, including: Evaluation objectives, evaluation tools, evaluation results, and evaluation follow-up plans have been carried out properly. (5) Obstacles in the Implementation of Strategies to improve the quality of teaching English speaking skills at Pondok Senior High School, including: HR Barriers, Learning Facilities Barriers, Learning Media Barriers, and Cost Barriers have been given a good solution. (6) Innovative efforts made to improve the quality of English speaking skills at Pondok Senior High School, include: Super camp and English E-learning have been well implemented IThe concusion is management of learning English on speaking skill is effective.